Guillain‐Barré syndrome (GBS) in a tertiary general hospital at Yangon, Myanmar. Issue 2 (18th January 2022) - Ohnmar, Ohnmar; Hlaing, Kyaw Phyo; Win, Zin Nwe; Aung, Yan Lynn; Tun, Zin Phyu; Htay, Kyawt Oo Kaythi; Thit, Win Min; Umapathi, Thirugnanam
Abstract: Aim: The aim of the study was to study the profile of Guillain‐Barré syndrome (GBS) patients admitted at Yangon General Hospital (YGH), Myanmar. Methods: Patients with flaccid quadriparesis due to GBS admitted to the Department of Neurology, YGH in 2019 were prospectively studied. Results: Ninety‐four GBS patients were recruited. Mean age was 36.2 years. Male to female ratio was 2.4:1. Patients were admitted 12.1 ± 14.8 days after disease onset. 46.8% were from outside the Yangon region. Peak incidence was in rainy season (47.9%). 62.8% reported symptoms suggestive of preceding infection: 45.7% unspecified fever, 3.2% upper respiratory infection, 8.5% diarrhea, and 5.3% fever with rash. 27.7% had bulbar and 44.7% had facial weakness. 5.3% had GBS/Miller Fisher syndrome overlap. Electrophysiologically, 50% were acute inflammatory demyelinating polyneuropathy (AIDP), 30% acute motor axonal neuropathy (AMAN), and 20% acute motor‐sensory axonal neuropathy (AMSAN). Maximum disability was reached at 5.6 ± 4.78 days from onset. The plateau phase lasted 12.12 ± 14.27 days. 13.8% required ventilator support. 64.9% of patients received limited manual plasma exchange, 9.6% standard plasma exchange, 4.3% intravenous immunoglobulin and 21.3% no specific treatment. 79.8% had good clinical recovery at 4 weeks from inclusion. Mortality was 0%. Severity at admission was identified as the only poor recovery predictor. Conclusion: Guillain‐Barré syndrome in a Yangon tertiary hospital peaked in rainy season and axonal GBS accounted for 50% cases. However, diarrhea was an uncommon antecedent. The good recovery was noted in 79.8% and largely predicted by severity of disease at admission.